Genomic Signatures Predict Migration and Spawning Failure in Wild Canadian Salmon - Miller, Kristina M; Li, Shaorong; Kaukinen, Karia H; Ginther, Norma; Hammill, Edd; Curtis, Janelle M.R; Patterson, David A; Sierocinski, Thomas; Donnison, Louise; Pavlidis, Paul; Hinch, Scott G; Hruska, Kimberly A; et al. (Science (American Association for the Advancement of Science), 2011)
Long-term population viability of Fraser River sockeye salmon (Oncorhynchus nerka) is threatened by unusually high levels of mortality as they swim to their spawning areas before they spawn. Functional genomic studies on biopsied gill tissue from tagged wild adults that were tracked through ocean and river environments revealed physiological profiles predictive of successful migration and spawning. We identified a common genomic profile that was correlated with survival in each study. In ocean-tagged fish, a mortality-related genomic signature was associated with a 13.5-fold greater chance of dying en route. In river-tagged fish, the same genomic signature was associated with a 50% increase in mortality before reaching the spawning grounds in one of three stocks tested. At the spawning grounds, the same signature was associated with 3.7-fold greater odds of dying without spawning. Functional analysis raises the possibility that the mortality-related signature reflects a viral infection.